Motivational Regulation in Foreign Language Learning - Li, Kun (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This text focuses on the motivational regulation in English language learning of Chinese college students. Considering the importance and necessity of motivational regulation study in foreign language learning, it systematically explores strategies used by Chinese college students to regulate motivation, taking into account student gender, specialty and English proficiency. The book considers self-regulated language learning, pointing out the impact that motivation, language learning strategies, and motivational regulation have on academic learning and achievement. Based on surveys of motivational regulation strategies used by Chinese college students as well as the differences in using motivational regulation strategies between high and low English achievers, the volume introduces models of self-regulated learning and provides a theoretical foundation for the study of motivational regulation.